Investigation of Pile Behavior Toward Abutment Construction using PLAXIS 3D: Case Study on Lembak Bridge - Clinton Girsang; Paulus Pramono Rahardjo; Aswin Lim (U Karst, 2021)
Soil  as  a  subgrade  foundation  under  embankment  construction often  creates  problems  in  terms  of  stability  and  settlement. Therefore, it needs improvement by using preloading embankment. This article presents the investigation of pile behavior towards two scenarios  of  abutment  construction  using  Plaxis  3D,  a  three- dimensional  finite  element  program.  The  use  of  two  scenarios  of analysis was Method A. The abutment construction phase conduct without using a preloading embankment, and Method B, where a preloading  embankment  constructs  before  the  abutment construction.  The  case  study  location  at  the  Lembak  bridge. Compare  the  analysis  results  with  the  measured  data.  Results showed that Method A and Method B's pile deflection yielded four times  and  one  point  six  times  larger  than  the  measure  data, respectively.  Hence,  it  indicates  that  Method  B  recommends  for future construction of bridge abutment.